Investigating Factors Affecting The Formation Of Informal Settlements In Iran - Amiri, Pedram; Ghanbari, Nowzar (The Turkish Online Journal of Design Art and Communication, 2016)
The consequence of rapid urbanization expansion in Iran, is the emergence of large cities and marginalized areas with abnormal housing and disorganized tissue. The main reasons for the formation of squatters in Tehran have been investigated in this study. Present study seeks to determine factors affecting the formation of the marginalizing using identify the situation of marginalized. Method of this study is documentation and survey method using a questionnaire. Conceptual and theoretical aspects have been examined using document method and survey method has been used to investigate the way of distribution and relations between dependent and independent variables. Sampling method is a quota in which questionnaires were distributed 200 households randomly. Independent variables include immigration, low income; high rent of housing and easier access to shelter and dependent variable of suburbanization. In the survey, after data collection using questionnaire and data processing with SPSS software, descriptive method and inferential statistics of chi-square has been used according to the level of variables measurement. Obtained results of the study indicate there is a relationship between attractions factor of Tehran and push factor of prior place of living with suburbanization.
Keywords: suburbanization; Tehran; immigration; income; housing